Problems of adoption of solar power and subsequent switching behavior: an exploration in India. Issue 1 (19th July 2021) - Roy, Subhadip; Mohapatra, Subhalaxmi
Abstract : Purpose: The challenges and factors of household adoption and the use of alternative energy sources have been a point of discussion among researchers. The purpose of this study is to apply a variant of the unified theory of adoption and use of technology (i.e. UTAUT 2) to explore the effect of various constructs that influence technology adoption on the consumers' intention to adopt (and use) solar power generators (SPG) at the household level and the subsequent switching behavior. Design/methodology/approach: Based on survey data collected from six cities in India (n = 1, 246), factor analysis and structural equation modeling are applied for data analysis and testing the study hypotheses. Findings: The results of the structural equation model found UTAUT constructs performance expectancy, effort expectancy, social influence and hedonic to positively affect behavioral intentions to adopt SPG. However, facilitating conditions and perceived value was not found to affect behavioral intentions to adopt SPG. Behavioral intentions to adopt SPG was found to positively influence the switching behavior. Research limitations/implications: The present study augments the domain of alternative energy usage behavior by applying the UTAUT 2 in the adoption of alternative energy sources (namely, solar) and subsequent switching behavior from traditional sources at the household level. Practical implications: The findings from the present study will guide the marketers and policymakers on the consumer attitudinal and behavioral aspects of solar energy usage at the household level and subsequent switching behavior. Originality/value: The present study is novel as it moves beyond household-level behavioral intention to use solar energy and includes the switching behavior to shift to solar power from traditional energy sources.